Molten salt electrosynthesis of Cr2GeC nanoparticles as anode materials for lithium-ion batteries - Pang, Zhongya; Tian, Feng; Xiong, Xiaolu; Li, Jinjian; Zhang, Xueqiang; Chen, Shun; Wang, Fei; Li, Guangshi; Wang, Shujuan; Yu, Xing; Xu, Qian; Lu, Xionggang; et al. (Frontiers in Chemistry, 2023)
The two-dimensional MAX phases with compositional diversity are promising functional materials for electrochemical energy storage. Herein, we report the facile preparation of the Cr2GeC MAX phase from oxides/C precursors by the molten salt electrolysis method at a moderate temperature of 700°C. The electrosynthesis mechanism has been systematically investigated, and the results show that the synthesis of the Cr2GeC MAX phase involves electro-separation and in situ alloying processes. The as-prepared Cr2GeC MAX phase with a typical layered structure shows the uniform morphology of nanoparticles. As a proof of concept, Cr2GeC nanoparticles are investigated as anode materials for lithium-ion batteries, which deliver a good capacity of 177.4 mAh g−1 at 0.2 C and excellent cycling performance. The lithium-storage mechanism of the Cr2GeC MAX phase has been discussed based on density functional theory (DFT) calculations. This study may provide important support and complement to the tailored electrosynthesis of MAX phases toward high-performance energy storage applications.